Maturation of Intestinal Oxygenation: A Review of Mechanisms and Clinical Implications for Preterm Neonates - Baukje M. Dotinga; Jonathan P. Mintzer; James E. Moore; Jan B. F. Hulscher; Arend F. Bos; Elisabeth M. W. Kooi (Frontiers Media S.A., 2020)
Nutrient requirements of preterm neonates may be substantial, to support growth and maturation processes in the presence of challenging post-natal circumstances. This may be accompanied by substantial intestinal oxygen requirements. Preterm neonates may not be able to meet these oxygen requirements, due to a developmental delay in intestinal oxygenation regulation mechanisms. This review summarizes the available literature on post-natal maturation of intestinal oxygenation mechanisms and translates these changes into clinical observations and potential implications for preterm neonates. The different mechanisms that may be involved in regulation of intestinal oxygenation, regardless of post-natal age, are first discussed. The contribution of these mechanisms to intestinal oxygenation regulation is then evaluated in newborn and mature intestine. Finally, the course of clinical observations is used to translate these findings to potential implications for preterm neonates.